2015
DOI: 10.1111/opo.12223
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vessel oxygen saturation and vessel diameter in high myopia

Abstract: The study demonstrated decreased retinal arteriole saturation and decreased difference in arterio-venous saturation as well as narrowing retinal vessel diameter in highly myopic eyes. Further studies are needed to determine if such changes play a role in the development of high myopia and its complications or occur as a consequence of tissue remodelling during axial elongation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 37 publications
(55 reference statements)
4
48
0
Order By: Relevance
“…Several studies have investigated the oxygen saturation of retinal vessels in patients with diabetes, glaucoma or RP, indicating that changes in retinal oxygen saturation and vessel diameter are associated with underlying microvascular dysfunction and preclinical structural changes in ocular (Tiedeman et al 1998;Michelson & Scibor 2006;Ramm et al 2014;Yao et al 2016). In high myopia eyes, Gao et al reported a lower oxygen saturation and narrowing diameter in retinal arterioles (Zheng et al 2015). This is consistent with the data obtained in the present study, demonstrating an unusual anatomy and physiology of the retina in high myopia eyes, and rising the concerns about any microcirculation abnormality inherent to ICL implantation surgery.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Several studies have investigated the oxygen saturation of retinal vessels in patients with diabetes, glaucoma or RP, indicating that changes in retinal oxygen saturation and vessel diameter are associated with underlying microvascular dysfunction and preclinical structural changes in ocular (Tiedeman et al 1998;Michelson & Scibor 2006;Ramm et al 2014;Yao et al 2016). In high myopia eyes, Gao et al reported a lower oxygen saturation and narrowing diameter in retinal arterioles (Zheng et al 2015). This is consistent with the data obtained in the present study, demonstrating an unusual anatomy and physiology of the retina in high myopia eyes, and rising the concerns about any microcirculation abnormality inherent to ICL implantation surgery.…”
Section: Discussionsupporting
confidence: 92%
“…; Zheng et al. ). This observation implied the ultrastructure changes of retina microcirculation in high myopia patients.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations